Representing translation procedures in translated Indonesian cultural terms into English of online news media - Rodiyah, Siti (ELT Forum: Journal of English Language Teaching, 2020)
Translating cultural terms needs proper procedures since each of culture has linguistics elements to be expressed between one language to other ones. Problems then may appeared in understanding cultures. It should do not be a big deal, because understanding cultures of one language to other ones can be easily resolved by translation and its proper procedures. Qualitative approach with content analysis used in this study to observe (1) The Indonesian Cultural Terms which those are translated into English on the Jakarta Post’s (JP) Online News and (2) The translation procedures used in replacing the Indonesian Cultural Terms into English. Based on the data analysis, 21 cultural terms found in this study as the data. First, the translated Indonesian cultural terms into English on the JP’s Online News are categorized into material, ecology, habit and festival. Second, the translation procedures used in replacing Indonesian cultural terms found in this study are couplets, single procedures that have been used such as literal translation, transference or loan word plus explanation, and translation by a more general word. There are many studies applied to observe translation and cultures on artworks of literature or cultural terms in any object from English into Indonesian language. While this study also concerns on both issues, culture and translation but it represents Indonesian Cultural Terms translated into English and the translation procedures used in replacing the Indonesian cultural terms in order to at least acknoledging Indonesian cultures through news widely.